2011
DOI: 10.1002/elps.201100123
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and efficient protein enzymatic digestion: An experimental comparison

Abstract: The major objective of proteomics is to identify and examine the large numbers of proteins extracted from complex biological systems. This is generally achieved by combining various techniques of protein separation with a mass spectrometric analysis of proteins that are digested enzymatically. Recently, several alternatives to this standard protocol have been developed for efficient and fast protein digestion. One option is the use of modified trypsin instead of native trypsin for the in-gel digestion of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, the conventional enzymatic digestion method is slow and requires overnight incubation, which can be another time-consuming step. Protocols for fast protein digestion have been introduced, such as digestion using modified enzymes [31], microwave digestion [3234], ultrasonic-assisted protein digestion [3538] and proteolysis accelerated by infrared radiation [3840]. Results have been shown that protein digestion can be finished in minutes without reducing efficiency and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conventional enzymatic digestion method is slow and requires overnight incubation, which can be another time-consuming step. Protocols for fast protein digestion have been introduced, such as digestion using modified enzymes [31], microwave digestion [3234], ultrasonic-assisted protein digestion [3538] and proteolysis accelerated by infrared radiation [3840]. Results have been shown that protein digestion can be finished in minutes without reducing efficiency and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A protocol has recently been published describing very fast (~10 min) and selective cleavage of proteins by microwave irradiation, but hydrolysis is limited to the N‐terminal peptide bond of aspartic acid residue only. Other methods are also available for the fast cleavage of proteins supported by sonification or infrared irradiation . With the judgment from our experiments, the time necessary for successful identification of longer peptides or small proteins by ETD/PTR reaction is fairly shorter than this on the basis of the protein cleavage with subsequent LC‐MS/MS technique application. Total cost of the equipment.…”
Section: Discussionmentioning
confidence: 94%
“…Other methods are also available for the fast cleavage of proteins supported by sonification or infrared irradiation. [15] With the judgment from our experiments, the time necessary for successful identification of longer peptides or small proteins by ETD/PTR reaction is fairly shorter than this on the basis of the protein cleavage with subsequent LC-MS/MS technique application. 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, high concentration of trypsin could lead to autodigestion that interferes with target protein analysis (41). To achieve a high digestion efficiency within a short digestion time, several alternative approaches have been developed, including ultrasound-, high pressure-, infrared- and microwave-assisted digestions (42-46), as well as on-column digestion using immobilized enzyme (47, 48). The latter strategy is particularly interesting because it can be performed online with MS.…”
Section: Resultsmentioning
confidence: 99%